Women in Arab society : work patterns and gender relations in Egypt, Jordan, and Sudan - Shami, Seteney Khalid; taminian , lucine; A. morsy , Soheir .; El bakri , Zeinab b; M. kameir , elwathig; Unesco (Providence, R.I., USA : Berg ; Paris, France : Unesco, 1990)
Based on the results of a non-governmental research project sponsored by UNESCO, this volume examines the impact of social and economic changes on patterns of women's work and on value systems concerning their social position in Arab societies. Case studies are drawn from Egypt, Jordan and Sudan.
Part 1 Women's participation in the Jordanian labour force - a comparison of rural and urban patterns, Dr Seteney Shami and Lucine Taminian: women's work in Jordan - case studies; rural case study - the southern Jordan valley; urban case study - squatter areas in Amman. Part 2 Women, work and gender ideology - a study in Egyptian political economic transformation, Dr Soheir A.Morsy: theoretical considerations; Egyptian state policies, agrarian transformation and rural women (1952-1981) - a historical note; Fatiha in 1974/75 - small-holder familial production; Bahiya in 1980/81 - regional labour migration and familial production. Part 3 Ways and means by which women paricipate in economoc and political life in a Sudanese urban and rural communities - the case of Saganna in Khartoum and Wad Al-Asha village in the Gezira area, Dr Zinab B.El-Bakri and Dr El-Wathig M.Kameir: women's studies in Sudan; Sudanese political economy - the dynamics of urban and rural society; the general position of Sudanese women; lives of women and their families in Saganna, Khartoum town; lives of women and their families in the village of Wad Al-Asha; comparing women in both communities.
Includes bibliographical references.
Keywords: Rural women -- Employment -- Arab countries -- Case studies; Rural women -- Employment -- Egypt -- Case studies; Women in agriculture -- Egypt -- Case studies; Rural women -- Employment -- Jordan -- Case studies; Women in agriculture -- Jordan -- Case studies; Rural women -- Employment -- Sudan -- Case studies; Women in agriculture -- Sudan -- Case studies